Administrative-law regulation safety of civil aviation - Жмур, Наталія Володимирівна; Єряшов, Євген Кузьмович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
This article is devoted to consideration of a comprehensive concept a safety of civil aviation and its elements. Also presents own definition of individual elements safety of civil aviation and the concept of administrative- law regulation of civil aviation safety In the context of analysis the norms of the Air Code of Ukraine and academic literature the author considers an aviation safety as a complex legal phenomenon that, on the one hand is a relatively stable condition, and on another consists of five elements. Аn environmental safety, economic safety and information safety should be given a definition and included in the Article 1 of the Air Code of Ukraine. The article provided the following definition of administrative-law regulation safety of civil aviation: it is carried out by the State overbearing influence on the operators of aircraft and other aviation activities by adopting regulations varying legal force (as well as authorization in to national legislation regional and international agreements) regarding a safe usage of aviation objectives in order to ensure of a safety of civil aviation.